Tioman virus, a paramyxovirus of bat origin, causes mild disease in pigs and has a predilection for lymphoid tissues. - Yaiw, K.C.; Bingham, John; Crameri, Gary; Mungall, Bruce; Hyatt, Alex; Yu, Meng; Eaton, Bryan; Shamala, Devi; Wang, L.F.; Thong Wong, Kum (American Society for Microbiology, 2008)
Disease manifestation, pathology, and tissue tropism following infection with Tioman virus (TioPV), a newly isolated, bat-derived paramyxovirus, was investigated in subcutaneously (n = 12) and oronasally (n = 4) inoculated pigs. Pigs were either asymptomatic or developed pyrexia, but all of the animals produced neutralizing antibodies. The virus (viral antigen and/or genome) was detected in lymphocytes of the thymus, tonsils, spleen, lymph nodes and Peyer's patches (ileum), tonsillar epithelium, and thymic epithelioreticular cells. Virus was isolated from oral swabs but not from urine. Our findings suggest that the pig could act as an intermediate or amplifying host for TioPV and that oral secretion is a possible means of viral transmission.